Diagnostic Accuracy of Gene X-pert MTB/RIF for Tuberculous Pleural Effusion Compared to Adenosine Deaminase (ADA) at Haji Adam Malik General Hospital Medan - Muhammad Zainul A; Fajrinur Syahrani; Siagian, Parluhutan; Eyanoer, Putri Chairani (Talenta Publisher, 2019)
Indonesia is one of the few countries in the world with very high burden of tuberculosis (TB). Tubercular pleural effusion (Pleural TB) is the most common form of extra-pulmonary TB, however the remains a common clinical challenge. This research from May 2017 through September 2017 a total of 42 patients with exudative lymphocytic pleural effusions suspected to pleural tuberculosis were enrolled in this study. Adenosine deaminase (ADA) and Gene X-pert were examined from pleural fluid. Diagnosis was made clinically or based from sputum/pleural fluid culture. The result of this research showed out of all participants, 64,3% (27/42) had ADA in positive level (>40 IU/L) and 31% (13/24) had Gene X-pert positive Mycobacterium Tb. The Gene X-pert sensitivity was 40.7% with specificity 86.6%, PPV and NPV were 44.8% and 57.1% respectively. Kappa Compatibility study show that Gene X-pert point was 0.227 (p 0.066). The usefulness of Gene X-pert to diagnose pleural TB is limited by its poor sensitivity. Gene X-pert cannot be used as single diagnostic tool for tuberculous pleural effusion